Uma proposta de adaptação de Canvas para modelos de projeto de pesquisa - Silva, Hiago Araujo (2019)
Learning is a process as old as human existence itself and is constantly developed through the contributions of researchers and educators. During the learning and research process students, teachers and advisors rely on technical and pedagogical tools. However, when there is a need to expand knowledge, these tools are replaced and for reasons such as: geographical and social positions are different in each context. In order to make better use of such a process, it is necessary to constantly adapt teaching and research practices to the context in which they are inserted. Advisors, students and researchers seek to use auxiliary content creation and management tools that can extrapolate traditional artifacts such as documents that are generated at the beginning of research projects, thus generating a common mental model in the team, which in turn has greater synchrony and performance. As a proof of concept, a system proposal, the Research Project Model Canvas, was implemented and evaluated, adapting already consolidated management and project creation methodologies to the context of research projects.